Comparison of DSTATCOM Performance for Voltage Sag Alleviation - Miska Prasad; Ashok Kumar Akella (Institute of Advanced Engineering and Science, 2016)
This paper describes the comparative analysis of three different control techniques of distributed flexible AC transmission system (DFACTS) controller called as distributed static synchronous compensator (DSTATCOM), aimed at power quality (PQ) enhancement in terms of voltage sag mitigation in a three-phase four-wire (3p4w) distribution system. A DSTATCOM is one of the major power quality improvement devices which consist of a DC energy source, a voltage source inverter (VSI), a filter, a coupling transformer and the control system. The control strategy based on synchronous reference frame (SRF) theory, instantaneous active and reactive current (IARC) theory and propositional-integral (PI) controller has been used for reference current generation of voltage source inverter (VSI) based DSTATCOM. The SRF, IARC and PI control based DSTATCOM is validated through dynamic simulation in a MATLABenvironment under linear as well as nonlinear loads.